Comparative Efficacy of Angiotensin II Type 1 Receptor Blockers Against Ventilator‐Induced Diaphragm Dysfunction in Rats - Stephanie E. Hall; Bumsoo Ahn; Ashley J. Smuder; Aaron B. Morton; J. Matthew Hinkley; Michael P. Wiggs; Kurt J. Sollanek; Hayden Hyatt; Scott K. Powers (Wiley, 2021)
Mechanical ventilation (MV) is a life‐saving intervention for many critically ill patients. Unfortunately, prolonged MV results in the rapid development of inspiratory muscle weakness due to diaphragmatic atrophy and contractile dysfunction (termed ventilator‐induced diaphragm dysfunction (VIDD)). Although VIDD is a major risk factor for problems in weaning patients from MV, a standard therapy to prevent VIDD does not exist. However, emerging evidence suggests that pharmacological blockade of angiotensin II type 1 receptors (AT1Rs) protects against VIDD. Nonetheless, the essential characteristics of AT1R blockers (ARBs) required to protect against VIDD remain unclear. To determine the traits of ARBs that are vital for protection against VIDD, we compared the efficacy of two clinically relevant ARBs, irbesartan and olmesartan; these ARBs differ in molecular structure and effects on AT1Rs. Specifically, olmesartan blocks both angiotensin II (AngII) binding and mechanical activation of AT1Rs, whereas irbesartan prevents only AngII binding to AT1Rs. Using a well‐established preclinical model of prolonged MV, we tested the hypothesis that compared with irbesartan, olmesartan provides greater protection against VIDD. Our results reveal that irbesartan does not protect against VIDD whereas olmesartan defends against both MV‐induced diaphragmatic atrophy and contractile dysfunction. These findings support the hypothesis that olmesartan is superior to irbesartan in protecting against VIDD and are consistent with the concept that blockade of mechanical activation of AT1Rs is a required property of ARBs to shield against VIDD. These important findings provide a foundation for future clinical trials to evaluate ARBs as a therapy to protect against VIDD.